Realism in the Portrayal of Indian Women in Shashi Deshpande’s Novels - Kumar, Mahesh (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 2 (2020): Journal of Advanced Research in Humanities and Social Science, 2020)
Shashi Deshpande is one of the foremost novelists who showcased to us the real picture of our society projecting women’s subjugation realistically. Her women characters are influenced by the changing times and as such they are not content with the traditional roles which have been assigned to them. The roles of mother, daughter, sister, wife and daughter-in law are reinvestigated by the protagonists of Shashi Deshpande. In the novel women are the victims as they have silenced themselves but, in the end, they come out of their shells of silence and want to articulate themselves. The winds of liberation and change have been blowing and the novels of Deshpande, though not having closed endings, end on the note of not despair but hope. Shashi Deshpande is hopeful that the lives of these myriads of women will definitely transform one day. The present novel “The Binding Vine” is actually a mirror of the Indian society. It has Urmila as a protagonist who, unlike previous heroines, fights other women’s battles. She is a college lecturer and is married to Kishore who works in the Merchant Navy. In the beginning of the novel Urmila is grieving for the loss of her daughter. Her own suffering leads her to recognize the suffering of other women. She reads her mother-in-law Mira’s poems which present to her the true account of Mira’s life which represent the victimization of many other women. Mira is subjected to marital rape all night. Kalpana, Shakutai’s daughter is raped by her own uncle Prabhakar. Urmila sympathizes with her and fights for her when the hospital authorities try to transfer her to a far-off suburban hospital. Urmila is the true embodiment of the female bonding between women and the writer hints that women must join hands to fight their victimization. Once they are united no one can harras them in any manner. How to cite this article: Kumar M. Realism in the Portrayal of Indian Women in Shashi Deshpande’s Novels. J Adv Res Humani Social Sci 2020; 7(2): 27-31. DOI : https://doi.org/10.24321/2349.2872.202002